Hubungan antara Kecerdasan Emosional dengan Perilaku Agresif pada Siswa SMK - Titik Larasati; Tugimin Supriyadi; Rijal Abdillah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Aggressive behavior among students of Vocational High Schools (Sekolah Menengah Kejuruan/SMK) remains a common phenomenon and has the potential to disrupt the learning process as well as social relationships within the school environment. One psychological factor believed to be related to the emergence of aggressive behavior is emotional intelligence. This study aimed to examine the relationship between emotional intelligence and aggressive behavior among SMK students in the Bekasi City area. This research employed a quantitative approach with a correlational method. The research participants consisted of 96 SMK students aged 16–18 years who were selected using a purposive sampling technique. The research instruments were an emotional intelligence scale and an aggressive behavior scale, both of which met the criteria of validity and reliability. Data were analyzed using Kendall’s Tau B correlation test because the data were not normally distributed. The results showed a significant relationship between emotional intelligence and aggressive behavior, with a correlation coefficient of 0.299 (p < 0.001), indicating a positive relationship with low to moderate strength. The categorization results indicated that most students had a high level of emotional intelligence; however, at the same time, aggressive behavior was also predominantly in the high category. These findings suggest that emotional intelligence is related to aggressive behavior, but it is not the only factor influencing it. Therefore, a more comprehensive approach that considers environmental, social, and psychological factors is needed to reduce aggressive behavior among SMK students.